I Wayan Geria: Penari, Pencipta, dan Guru Seni Pertunjukan Bali - Ayu Ketut Putri Rahayuning (EKSPRESI, 2010)
I Wayan Geria: Dancer, Composer, and Balinese Performing Art Teacher. This study aims at comprehending I Wayan Geria’s important role and existence as a Balinese performing artist. The result of this research indicates that I Wayan Geria is an eminent dancer, a strong dance creator, and a highly respected dance teacher. As a dancer, Geria is a model for an artist with high dedication to his art, with an endless effort to improve his artistic skill. As a dance creator, Geria always dedicates his new works to his village and community. As a dance teacher, Geria always teaches his student with high discipline and provides them with the best training.Keywords: Balinese dancer, dance creator, performing arts.